2013
DOI: 10.1177/0091270011434157
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Breath Test for Monitoring Adherence to Vaginal Administration of Antiretroviral Microbicide Gels

Abstract: Adherence to microbicide gel use is critical to optimizing effectiveness in preventing human immunodeficiency virus transmission. The authors hypothesized that ester taggants added to vaginal gels would generate exhaled alcohol and ketone metabolites and provide a "breath test" for vaginal gel use. This 2-arm (vaginal and dermal), randomized, participant-blinded, pilot study tested this hypothesis. On 8 visits, healthy women (n = 8) received intravaginal taggant (2-butyl acetate, 2-pentyl acetate, isopropyl bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…32 Laboratory research also is needed to better characterize and improve the use of existing SBMs. For example, the Centers for Disease Control and Prevention is conducting preliminary testing on the detection of PSA in rectal swabs from men as a marker of semen exposure during unprotected receptive anal intercourse.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…32 Laboratory research also is needed to better characterize and improve the use of existing SBMs. For example, the Centers for Disease Control and Prevention is conducting preliminary testing on the detection of PSA in rectal swabs from men as a marker of semen exposure during unprotected receptive anal intercourse.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Given past studies that showed the chemical taggants used for the breath test approach in vaginal gel products caused an unfavorable taste for some women [14, 15], survey respondents were asked an additional question about women’s acceptance of the method if they knew it would result in an unfavorable taste. Over three-quarters (78.6%) of respondents said that it was very likely or somewhat likely that women would refuse the method if this was the case (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Newer EAMs are in development, including ingestion monitors [59] and metabolite detectors [60]. The best-described ingestion monitor, Proteus, involves pills embedded or encapsulated with a microchip that, upon contact with digestive fluids, transmits a signal to a transponder (a disposable patch) worn by an individual.…”
Section: Future Eamsmentioning
confidence: 99%